Genetic Analysis of Open Pollinated Seed Progeny of Guinea Grass Clones - Sally Joseph V (Department of Plant Breeding, College of Agriculture, 1988)
Open pollinated seeds collected from six guinea grass clones were used for genetic evaluation of progeny through analysis of variance and covariance, coefficient of variation, heritability, genetic advance, simple correlation studies and D2 analysis. The progeny of pubescent clones were found segregating into pubescent and glabrous types indicating the possibility of producing superior hybrid guinea grass clones using glabrous the character as marker gene. The study on the mean performance of individual traits revealed the overall superiority of the mutant clone MC-16 over others in green fodder yield, tiller counts, leaf-stem ratio and dry matter yield. But MC-2, which was on par with MC-16 in green fodder yield, was found superior over MC-16 in quality characters like crude fibre content and crude protein content. The estimates of GCV and PCV were low for all characters. Among the nine characters studied the highest estimates of GCV and PCV were obtained for dry matter yield indicating scope for improvement of that character through selection. Highgest fodder yield showed positive correlation with all the other characters except leaf-stem ratio and inflorescence count. Dry matter yield was found contributing maximum towards green fodder yield. Plant height and tiller counts have also shown positive correlation with green fodder yield. The data on interrelations among different characters have shown that the different characters have shown that the different associations among tiller counts, dry matter yield, plant height, width of leaves and crude fibre content were positive. This has suggested the possibility of simultaneous improvement of these characters in a selection programme involving any one of these traits. Through divergence analysis of the six varieties were grouped into three genetic constellations with the assumption that the varieties within the cluster had smaller D2 values among themselves than varieties between the clusters. The intercluster distance was maximium between cluster II and III showing considerable genetic distance between these groups. The inflorescence count contributed maximum towards divergence followed by crude protein content, tiller counts and height of plants indicating that selection of parents differing in these characters will result in the production of divergent material.